Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a. Ta có:\(\frac{x}{y}\sqrt{\frac{y^2}{x^4}=}\) \(\frac{x}{y}.\frac{\left|y\right|}{x^2}=\frac{x.y}{x^2y}\)\(=\frac{1}{x}\)(Vì \(x\ne0;y>0\))
b \(3x^2\sqrt{\frac{8}{x^2}}=3x^2\frac{2\sqrt{2}}{\left|x\right|}=\frac{6x^2\sqrt{2}}{-x}=-6x\sqrt{2}\)( Vì \(x< 0\))
P=3*\(\sqrt{4\cdot\left(x^3\right)^2}\)-3x^3
=3*2*x^3-3*x^3
=3x^3
\(P=3\sqrt{4x^6}-3x^3=\sqrt{36x^6}-3x^3=|6x^3|-3x^3=-9x^3\left(x< 0\right)\)
a) \(4x-\sqrt{x^2-4x+4}=4x-\sqrt{\left(x-2\right)^2}=4x-\left(x-2\right)=3x+2\)
b) \(3x+\sqrt{9+6x+x^2}=3x+\sqrt{\left(x+3\right)^2}=3x-\left(x+3\right)=2x-3\)
c) \(\frac{x+6\sqrt{x}+9}{x-9}=\frac{\left(\sqrt{x}+3\right)^2}{\left(\sqrt{x}-3\right)\left(\sqrt{x}+3\right)}=\frac{\sqrt{x}+3}{\sqrt{x}-3}\)
d) \(\frac{\sqrt{x^2+4x+4}}{x+2}=\frac{\sqrt{\left(x+2\right)^2}}{x+2}=\frac{\left|x+2\right|}{x+2}\)( 1 )
với x < -2 thì : \(\left(1\right)\Leftrightarrow\frac{-\left(x+2\right)}{x+2}=-1\)
với x > -2 thì : \(\left(1\right)\Leftrightarrow\frac{\left(x+2\right)}{x+2}=1\)
a)\(\)https://www.cymath.com/answer?q=2sqrt(27)-6sqrt(4%2F3)%2B3%2F5sqrt(75)
\(M=2\sqrt{27}-6\sqrt{\frac{4}{3}}+\frac{3}{5}\sqrt{75}=2\sqrt{3^2.3}-6\sqrt{\frac{2^2.3}{3^2}}+\frac{3}{5}\sqrt{5^2.3}=.\)
\(=6\sqrt{3}-4\sqrt{3}+3\sqrt{3}=5\sqrt{3}\)
\(P=\frac{2}{x-1}\sqrt{\frac{x^2-2x+1}{4x^2}}.Với...0< x< 1\Leftrightarrow\) \(P=\frac{2}{x-1}\sqrt{\frac{\left(x-1\right)^2}{\left(2x\right)^2}}=\frac{2}{(x-1)}.\frac{\left(1-x\right)}{2x}=\frac{-1}{x}.\)
a/ \(=4x-\sqrt{\left(x-2\right)^2}=4x-x+2=3x+2\)
b/ \(=3x+\sqrt{\left(x+3\right)^2}=3x+x+3=4x+3\)
c/ xem lại đb
d/ \(=\frac{\sqrt{\left(x+2\right)^2}}{x+2}=\frac{x+2}{x+2}=1\)
\(\sqrt{72a^8\left(x^2-4x+4\right)}=\sqrt{72a^8\left(x-2\right)^2}=\sqrt{72}a^4|\left(x-2\right)|=\sqrt{72}a^4\left(2-x\right)\)
\(\sqrt{40x^6\left(a^2+6a+9\right)}=\sqrt{40x^6\left(x+3\right)^2}=\sqrt{40}|x^3\left(x+3\right)|=\sqrt{40}.\left(-x^3\right)\left(3-x\right)\)
\(=-\sqrt{40}x^3\left(3-x\right)\)
\(=\frac{2\sqrt{x}}{x-3}.\frac{\sqrt{\left(x-3\right)^2}}{\sqrt{x}}=\frac{2\left(x-3\right)}{x-3}=-2\)
a)\(x+3+\sqrt{x^2-6x+9}\)
\(=x+3+\sqrt{\left(x-3\right)^2}\)
\(=x+3+x-3\)
\(=2x\)
b)\(\sqrt{x^2+4x+4}-\sqrt{x^2}\)
\(=\sqrt{\left(x+2\right)^2}-x\)
\(=x+2-x\)
=2
c)\(\sqrt{\frac{x^2-2x+1}{x-1}}\)
\(=\sqrt{\frac{\left(x-1\right)^2}{x-1}}\)
\(=\sqrt{x-1}\)
gọi bieur thức đó là A ta được :
A = 6 | x3 | - 3x3
Vì x < 0 nên A = -6x3 - 3x3 = -9x3